Peningkatan Produksi Azadirahtin dalam Kultur Suspensi Sel Azadirachta indica A.Juss melalui Penambahan Skualen - Zulfa Zakiah; Erly Marwani; Arbayah H. Siregar (Institut Teknologi Bandung, 2003)
One of the methods to enhance the secondary metabolite content in plant tissue culture is precursor feeding. The study on azadirachtin enhancement in cell suspension culture of Azadirachta indica A.Juss was conducted by supplying squalene as precursor. Callus were induced on Murashige-Skoog solid medium with addition of 0,5Î¼M 2,4-dichlorophenoxy acetic acid (2,4-D) and 1,0Î¼M 6-benzylaminopurine (BAP). Callus were subcultured to Murashige-Skoog liquid medium with addition of 0,1Î¼M 2,4-D and 1,0Î¼M BAP. The cell suspension cultures were subcultured three times, and then treated each with 10, 100, and 1000Î¼M of squalene. Azadirachtin content was measured at 0, 2, 4, 6, 8, 10 and 12 days after feeding using HPLC (High Pressure Liquid Chromatography) with methanol:water (6:4) as mobile phase. The results showed that the highest azadirachtin content in cell suspension culture before supplying squalene was 0,041 g/g cell dry-weight (dw) at the age of 8 days culture. The increment of azadirachtin content in cell and medium was significantly influenced by squalene concentration and age of culture. The highest azadirachtin content after feeding in the cell mass (0,076 Â± 0,006 g/g dw) and in the medium (0,229 Â± 0,003 mg/L)was achieved on supplying 100Î¼M squalene to 10 and 12 days culture.